Indian gooseberry (Emblica officinalis Gaertn) drink spiked with spices-Immunomodulatory properties - Gomez, Saji; Prabha, Silpa; Kanjoormana Aryan, Manu; Raghavamenon, Achuthan; Kuruvila, Bintu; Anjali Chandran (International journal of health sciences, 2024)
Indian gooseberry juice (20% (v/v) was reconstituted with 5% ginger juice (v/v) extracted from freshly harvested rhizomes, 2% each of turmeric rhizome powder and black pepper powder (w/v), followed by raising the total soluble solids to 130Brix by adding sugar syrup. Finally, 5% acid lime juice of 2.45% of titratable citric acid was added to the entire mixture in order to impart a fruity flavour to the product. The entire mixture was homogenized at 175 Bar (2500 psi) with a speed of 235 rpm and was subsequently pasteurized at 1000C for 10 minutes. LC-MS/MS analysis detected phenolic compounds (2-galloyl glucose, 2,6-galloyl glucose), capsaicinoids, curcuminoids, gingerol and shogaol. Though cyclophosphamide significantly inhibited the relative weight of thymus from 0.193 ± 0.048 in normal mice to 0.077 ± 0.034, treatment with the herbal drink significantly increased the relative weight of thymus, showing increased T cell differentiation. Mice treated with the drink showed marginal increase in the WBC count, indicating recovery of immunity. Recovery of bone marrow cellularity in mice fed with the herbal drink was directly proportional to the concentration of the drink. Increase in a-esterase activity was also directly proportional to the concentration of herbal beverage.